63 documents the government doesn't want you to read - Ventura, Jesse (Skyhorse Pub., 2011)
In this incredible collection of actual government documents, Ventura, the ultimate nonpartisan truth-seeker, proves beyond any doubt that the official spin of numerous government programs is bull. He and Russell walk readers through 63 of the most incriminating programs to reveal what really happens behind the closed doors.